A novel antimicrobial therapy for the control of Aeromonas hydrophila infection in aquaculture using marine polysaccharide coated gold nanoparticle. (September 2017) - Vijayakumar, Sekar; Vaseeharan, Baskaralingam; Malaikozhundan, Balasubramanian; Gobi, Narayanan; Ravichandran, Samuthirapandian; Karthi, Sellamuthu; Ashokkumar, Balasubramaniem; Sivakumar, Natesan
Abstract: In the present study, we prepared fucoidan coated Au-NPs (Fu-AuNPs), and examined its antimicrobial activity against Aeromonas hydrophila . The green synthesized Fu-AuNPs were bio-physically characterized by Ultraviolet–visible (UV-Vis) spectroscopy, X-ray Diffraction (XRD), Fourier Transform Infrared spectroscopy (FTIR), Higher Transmission Electron Microscopy (HR-TEM), Zeta potential analysis and Energy Dispersive X-ray spectroscopy (EDX). Fu-AuNPs were crystalline in nature, spherical to triangular in shape, with particle size ranging within 10–100 nm. The synthesized Fu-AuNPs at 100 μg mL −1 showed inhibition zone against A. hydrophila (23.2 mm) which is much higher than that of commercial antibiotic chloramphenicol (17.3 mm). The biofilm inhibitory activity of Fu-AuNPs against Gram negative ( Aeromonas hydrophila ) was higher. Light and confocal laser scanning microscopic observations showed that the Fu-AuNPs at 100 μg mL −1 inhibited the biofilm of A. hydrophila . The cytotoxicity study indicated that Fu-AuNPs were effective in inhibiting the viability of human cervical cancer cells (HeLa) at 100 μg mL −1 . In another experiment, the antibacterial effect of Fu-AuNPs on tilapia, Oreochromis mossambicus were evaluated in vivo. The mortality rate of O. mossambicus infected by A. hydrophila was much higher (90%), whereas, the mortality of O. mossambicus that received Fu-AuNPs followed by challenge with A. hydrophia was reduced to 30%. This study concludes that Fu-AUNPs are effective in the control of A. hydrophila infections in O. mossambicus . Graphical abstract: Highlights: Gold nanoparticles were synthesized using marine polysaccharide fucoidan from Fucus vesiculosus (Fu-AuNPs). Fu-AuNPs were physico-chemically characterized by UV-Vis spectroscopy, XRD, FTIR, HR-TEM, EDX and zeta potential. Fu-AuNPs exhibited antibacterial and antibiofilm activity against A. hydrophila. Fu-AuNPs showed anticancer activity against human cervical cancer (He La) cells. Fu-AuNPs significantly increased the survival of O. mossambicus following infection with A. hydrophila.